We will follow the rules** **for
simplifying an expression using PEMDAS rules - involving integers for solving
order of operations.

Follow the order of operation as:

**1.** Parenthesis → Find the things inside the **Parenthesis** part before Exponent, Multiply, Divide, Add or Subtract.

**For example:**

6 × (11 + 3)

= 6 × 14

= 84

**2.** Exponent → Then do the **Exponent** part (Powers, Roots, etc.,)
before Multiply, Divide, Add or Subtract.

**For
example:**

7 × 8 × 8 + 2

= 7 × 64 + 2

= 448 + 2

= 450

**3.** Multiplication/ Division → Then do **Multiply** or **Divide** part before Add or Subtract start from left to right.

**For example:**

5 × 3 + 6 ÷ 3

= 15 + 6 ÷ 3

= 15 + 2

= 17

**4.** Addition/Subtraction → At last do **Add **or **Subtract** start from left to right.

**For example:**

16 + (4 - 1) × 6

= 16 + 3 × 6

= 16 + 18

= 34

Worked-out
problems for solving PEMDAS rules - involving integers:

**Simplify using PEMDAS rule:**

**(a)** 18 - 24 ÷ 6
+ 3 × 5

**Solution:**

18 - 24 ÷ 6 + 3 × 5

= 18 - 4 + 3 ×
5, (Simplifying ‘**division**’ 24 ÷ 6 =
4)

= 18 - 4 + 15, (Simplifying
‘**multiplication**’ 3 × 5 = 15)

= 14 + 15, (Simplifying ‘**subtraction**’ 18 - 4 = 14)

= 29, (Simplifying
‘**addition**’ 14 + 15 = 29)

**Answer: 29**

**(b)** 11 - [3 + 5
of (13 - 2 × 6)]

**Solution:**

11 - [3 + 5 of (13 - 2 × 6)]

= 11 - [3 + 5
of (13 - 12)], (Simplifying
‘**multiplication**’ 2 × 6 = 12)

= 11 - [3 + 5
of 1], (Simplifying inside the ‘**parenthesis**’
13 - 2 = 1)

= 11 - [3 + 5 ×
1], (Simplifying ‘**of**’)

= 11 - [3 + 5], (Simplifying
‘**multiplication**’ 5 × 1 = 5)

= 11 - 8, (Simplifying
‘**add**’ inside the ‘**square brackets**’ 3 + 5 = 8)

= 3, (Simplifying
‘**subtraction**’ 11 - 8 = 3)

**Answer: 3**

**(c)** 22 - 4 of
(7 - 2) + 4 × 5

**Solution:**

22 - 4 of (7 - 2) + 4 × 5

= 22 - 4 of 5 +
4 × 5, (Simplifying inside the ‘**parenthesis**’
7 - 2 = 5)

= 22 - 4 × 5 + 4 × 5

= 22 - 20 + 4 ×
5, (Simplifying ‘**of**’ 4 × 5 = 20)

= 22 - 20 + 20,
(Simplifying ‘**multiplication**’ 4 × 5
= 20)

= 2 + 20, (Simplifying
‘**subtraction**’ 22 - 20 = 2)

= 22, (Simplifying
‘**addition**’ 2 + 20 = 22)

**Answer: 22**

● **Related Concept **

● Decimals

● Conversion of Unlike Decimals to Like Decimals

● Decimal and Fractional Expansion

● Converting Decimals to Fractions

● Converting Fractions to Decimals

● H.C.F. and L.C.M. of Decimals

● Repeating or Recurring Decimal

● BODMAS/PEMDAS Rules - Involving Decimals

● PEMDAS Rules - Involving Integers

● PEMDAS Rules - Involving Decimals

● BODMAS Rules - Involving Integers

● Conversion of Pure Recurring Decimal into Vulgar Fraction

● Conversion of Mixed Recurring Decimals into Vulgar Fractions

**From PEMDAS Rules - Involving Integers to HOME PAGE**

**Didn't find what you were looking for? Or want to know more information
about Math Only Math.
Use this Google Search to find what you need.**

## New! Comments

Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.